Design of an active control suction tank for cavitation study on centrifugal pump [compact disc] - 293411 Khong, Chan Haur (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2006